PENGARUH PELATIHAN DAN PENGEMBANGAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT DAMAI KABUPATEN KUTAI BARAT - Julita julita (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study was to determine the effect of training and development at the Damai sub-district office on employee productivity. The type of research used is quantitative research with quantitative descriptive methods using questionnaires and multiple linear regression analysis tools, validity and reliability tests, correlation tests and determination tests. Test the hypothesis T test and F test and use the SPSS 21 tool to determine the effect and relationship of each variable. From the results of the analysis, it is known that the training and development variables simultaneously have a positive and significant influence on the work productivity of employees at the Damai District Office of West Kutai Regency. And of the two independent variables, namely training and development, the dominant variable is Development.